Creation of the Political Image of Edward Gierek in the Polish Film Chronicle – a National Aspect - Matura, Piotr (Vade Nobiscum, tom XXI/2019: Studia z historii gospodarczej, kulturowej i społecznej, 2019)
The creation of a political image is one of the main elements of the election campaign in democratic countries, and in the authoritarian regimes of propaganda. For an effective politician, it can be extremely helpful in building his position in the country, or in the world. The figure of Edward Gierek, after he took office of the First Secretary of the Central Committee of the Polish United Workers’ Party, was very often present in various media. He also could not be miss in the Polska Kronika Filmowa. The new “First” definitely appreciated the importance of his positive presentation in the mass media, what was evident in the quantity and specificity of the materials associated with it. This paper deals with the analysis of how the First Secretary of the Central Committee of the PUWP was presented in this medium, presents certain patterns of the creation of his image, and outlines the changes taking place in it over the years. The work includes specification of several planes and characteristic elements of the construction of Edward Gierek’s image in the national context. This article is also trying to capture the goals of this creation. The author used the available literature on the subject, dealing with the Polska Kronika Filmowa as well as the political image. He also analyzed the available film materials and, above all, assembly lists, which were a detailed description of the chronicle editing, including a list of intakes with a description, as well as a lector’s commentary.